Pengembangan Model Manajemen Literasi Sekolah untuk Peningkatan Capaian Rapor Pendidikan - Sarana Sarana; Suyanto Suyanto; Furqon Wahyudi; Sarana Sarana; Suyanto Suyanto; Furqon Wahyudi (Jurnal Riset Madrasah Ibtidaiyah (JURMIA), 2026)
Reading literacy is one of the essential 21st-century competencies measured through the national assessment and presented in the education report card as a basis for evaluating education quality and implementing data-driven planning at the school level. this study aims to identify an effective school literacy management model to improve education report card outcomes. the research employed a descriptive qualitative approach in schools with top literacy achievement rankings at the district and national levels in 2025, namely smp negeri 1 kunjang and smp negeri 3 wates in kediri regency, involving principals, the school literacy team, teachers, librarians, students, parents, and the community as research subjects. data were collected through in-depth interviews, participatory observation, and documentation, and analyzed using the miles and huberman interactive model with validity ensured through source and technique triangulation. the findings indicate that improvements in reading literacy are supported by integrated literacy management, including education report card–based planning, collaborative organization across stakeholders, sustainable and contextual literacy activities centered on students, and reflective evaluation based on program outcomes. the novelty of this study is the development of a school literacy management model based on the cycle of data–collaboration–contextual action–reflection, integrating management functions systematically for decision-making and continuous program improvement. the study concludes that data-driven, collaborative, contextual, and reflective management significantly contributes to improving reading literacy and provides contributions to the advancement of data-based educational management science, evidence-based school leadership practices, and innovation in education quality improvement policies.